Analisa Kemampuan Adaptasi Siswa Prakerin Terhadap Kedisiplinan dan Etos Kerja Industri: Studi Kasus Prakerin di PT. ATMI Solo - Albert Kurniawan; Valiant Lukad Perdana Sutrisno (Nozel : Jurnal Pendididikan Teknik Mesin, 2026)
This study aims to analyze students’ adaptation to industrial discipline and work ethic during industrial internships and to identify the supporting and inhibiting factors experienced by students at PT. ATMI Solo. This study employed a qualitative method with a case study approach. Data were collected through semi-structured interviews, participatory observation, and documentation using purposive sampling and snowball sampling techniques. Data analysis was conducted using the Miles and Huberman model. The results showed that students’ adaptation to industrial discipline and work ethic occurred gradually through continuous exposure to industrial work culture. Students learned to adjust to time discipline, job responsibilities, compliance with standard operating procedures (SOP) and occupational safety regulations (K3), as well as work quality standards. Supporting factors included guidance from industry supervisors, a supportive work environment, prior practical experience, and students’ learning motivation. Meanwhile, inhibiting factors included differences in students’ basic competencies, limited mastery of industrial technology, low mental readiness for work, and lack of motivation among some students.